Take 2,720/34,000=.0806. This means that 2,720 is 8.06% of the original number. In order to find the percentage of decrease, you take 100%-8.06%, which equals 91.94%. Your answer is 91.94%.
Answer:
83.1219512195
Step-by-step explanation:
Hope this helps!
Answer:
1/4 of them were rotten
rotten ones = 1/4 × 12 = 3
ones that weren't rotten = 12 - 3 = 9
Let's start from what we know.
![(1)\qquad\sum\limits_{k=1}^n1=\underbrace{1+1+\ldots+1}_{n}=n\cdot 1=n\\\\\\ (2)\qquad\sum\limits_{k=1}^nk=1+2+3+\ldots+n=\dfrac{n(n+1)}{2}\quad\text{(arithmetic series)}\\\\\\ (3)\qquad\sum\limits_{k=1}^nk\ \textgreater \ 0\quad\implies\quad\left|\sum\limits_{k=1}^nk\right|=\sum\limits_{k=1}^nk](https://tex.z-dn.net/?f=%281%29%5Cqquad%5Csum%5Climits_%7Bk%3D1%7D%5En1%3D%5Cunderbrace%7B1%2B1%2B%5Cldots%2B1%7D_%7Bn%7D%3Dn%5Ccdot%201%3Dn%5C%5C%5C%5C%5C%5C%0A%282%29%5Cqquad%5Csum%5Climits_%7Bk%3D1%7D%5Enk%3D1%2B2%2B3%2B%5Cldots%2Bn%3D%5Cdfrac%7Bn%28n%2B1%29%7D%7B2%7D%5Cquad%5Ctext%7B%28arithmetic%20%20series%29%7D%5C%5C%5C%5C%5C%5C%0A%283%29%5Cqquad%5Csum%5Climits_%7Bk%3D1%7D%5Enk%5C%20%5Ctextgreater%20%5C%200%5Cquad%5Cimplies%5Cquad%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5Enk%5Cright%7C%3D%5Csum%5Climits_%7Bk%3D1%7D%5Enk)
Note that:
![\sum\limits_{k=1}^n(-1)^k\cdot k^2=(-1)^1\cdot1^2+(-1)^2\cdot2^2+(-1)^3\cdot3^2+\dots+(-1)^n\cdot n^2=\\\\\\=-1^2+2^2-3^2+4^2-5^2+\dots\pm n^2](https://tex.z-dn.net/?f=%5Csum%5Climits_%7Bk%3D1%7D%5En%28-1%29%5Ek%5Ccdot%20k%5E2%3D%28-1%29%5E1%5Ccdot1%5E2%2B%28-1%29%5E2%5Ccdot2%5E2%2B%28-1%29%5E3%5Ccdot3%5E2%2B%5Cdots%2B%28-1%29%5En%5Ccdot%20n%5E2%3D%5C%5C%5C%5C%5C%5C%3D-1%5E2%2B2%5E2-3%5E2%2B4%5E2-5%5E2%2B%5Cdots%5Cpm%20n%5E2)
(sign of last term will be + when n is even and - when n is odd).
Sum is finite so we can split it into two sums, first
![S_n^+](https://tex.z-dn.net/?f=S_n%5E%2B)
with only positive trems (squares of even numbers) and second
![S_n^-](https://tex.z-dn.net/?f=S_n%5E-%20)
with negative (squares of odd numbers). So:
![\sum\limits_{k=1}^n(-1)^k\cdot k^2=S_n^+-S_n^-](https://tex.z-dn.net/?f=%5Csum%5Climits_%7Bk%3D1%7D%5En%28-1%29%5Ek%5Ccdot%20k%5E2%3DS_n%5E%2B-S_n%5E-)
And now the proof.
1) n is even.
In this case, both
![S_n^+](https://tex.z-dn.net/?f=S_n%5E%2B)
and
![S_n^-](https://tex.z-dn.net/?f=S_n%5E-)
have
![\dfrac{n}{2}](https://tex.z-dn.net/?f=%5Cdfrac%7Bn%7D%7B2%7D)
terms. For example if n=8 then:
![S_8^+=\underbrace{2^2+4^2+6^2+8^2}_{\frac{8}{2}=4}\qquad\text{(even numbers)}\\\\\\ S_8^-=\underbrace{1^2+3^2+5^2+7^2}_{\frac{8}{2}=4}\qquad\text{(odd numbers)}\\\\\\](https://tex.z-dn.net/?f=S_8%5E%2B%3D%5Cunderbrace%7B2%5E2%2B4%5E2%2B6%5E2%2B8%5E2%7D_%7B%5Cfrac%7B8%7D%7B2%7D%3D4%7D%5Cqquad%5Ctext%7B%28even%20numbers%29%7D%5C%5C%5C%5C%5C%5C%0AS_8%5E-%3D%5Cunderbrace%7B1%5E2%2B3%5E2%2B5%5E2%2B7%5E2%7D_%7B%5Cfrac%7B8%7D%7B2%7D%3D4%7D%5Cqquad%5Ctext%7B%28odd%20numbers%29%7D%5C%5C%5C%5C%5C%5C)
Generally, there will be:
![S_n^+=\sum\limits_{k=1}^\frac{n}{2}(2k)^2\\\\\\S_n^-=\sum\limits_{k=1}^\frac{n}{2}(2k-1)^2\\\\\\](https://tex.z-dn.net/?f=S_n%5E%2B%3D%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7D%282k%29%5E2%5C%5C%5C%5C%5C%5CS_n%5E-%3D%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7D%282k-1%29%5E2%5C%5C%5C%5C%5C%5C)
Now, calculate our sum:
![\left|\sum\limits_{k=1}^n(-1)^k\cdot k^2\right|=\left|S_n^+-S_n^-\right|= \left|\sum\limits_{k=1}^\frac{n}{2}(2k)^2-\sum\limits_{k=1}^\frac{n}{2}(2k-1)^2\right|=\\\\\\= \left|\sum\limits_{k=1}^\frac{n}{2}4k^2-\sum\limits_{k=1}^\frac{n}{2}\left(4k^2-4k+1\right)\right|=\\\\\\](https://tex.z-dn.net/?f=%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5En%28-1%29%5Ek%5Ccdot%20k%5E2%5Cright%7C%3D%5Cleft%7CS_n%5E%2B-S_n%5E-%5Cright%7C%3D%0A%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7D%282k%29%5E2-%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7D%282k-1%29%5E2%5Cright%7C%3D%5C%5C%5C%5C%5C%5C%3D%0A%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7D4k%5E2-%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7D%5Cleft%284k%5E2-4k%2B1%5Cright%29%5Cright%7C%3D%5C%5C%5C%5C%5C%5C)
![=\left|4\sum\limits_{k=1}^\frac{n}{2}k^2-4\sum\limits_{k=1}^\frac{n}{2}k^2+4\sum\limits_{k=1}^\frac{n}{2}k-\sum\limits_{k=1}^\frac{n}{2}1\right|=\left|4\sum\limits_{k=1}^\frac{n}{2}k-\sum\limits_{k=1}^\frac{n}{2}1\right|\stackrel{(1),(2)}{=}\\\\\\= \left|4\dfrac{\frac{n}{2}(\frac{n}{2}+1)}{2}-\dfrac{n}{2}\right|=\left|2\cdot\dfrac{n}{2}\left(\dfrac{n}{2}+1\right)-\dfrac{n}{2}\right|=\left|n\left(\dfrac{n}{2}+1\right)-\dfrac{n}{2}\right|=\\\\\\ ](https://tex.z-dn.net/?f=%3D%5Cleft%7C4%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7Dk%5E2-4%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7Dk%5E2%2B4%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7Dk-%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7D1%5Cright%7C%3D%5Cleft%7C4%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7Dk-%5Csum%5Climits_%7Bk%3D1%7D%5E%5Cfrac%7Bn%7D%7B2%7D1%5Cright%7C%5Cstackrel%7B%281%29%2C%282%29%7D%7B%3D%7D%5C%5C%5C%5C%5C%5C%3D%0A%5Cleft%7C4%5Cdfrac%7B%5Cfrac%7Bn%7D%7B2%7D%28%5Cfrac%7Bn%7D%7B2%7D%2B1%29%7D%7B2%7D-%5Cdfrac%7Bn%7D%7B2%7D%5Cright%7C%3D%5Cleft%7C2%5Ccdot%5Cdfrac%7Bn%7D%7B2%7D%5Cleft%28%5Cdfrac%7Bn%7D%7B2%7D%2B1%5Cright%29-%5Cdfrac%7Bn%7D%7B2%7D%5Cright%7C%3D%5Cleft%7Cn%5Cleft%28%5Cdfrac%7Bn%7D%7B2%7D%2B1%5Cright%29-%5Cdfrac%7Bn%7D%7B2%7D%5Cright%7C%3D%5C%5C%5C%5C%5C%5C%0A)
![=\left|\dfrac{n^2}{2}+n-\dfrac{n}{2}\right|=\left|\dfrac{n^2}{2}+\dfrac{n}{2}\right|=\left|\dfrac{n^2+n}{2}\right|=\left|\dfrac{n(n+1)}{2}\right|\stackrel{(2)}{=}\\\\\\\stackrel{(2)}{=} \left|\sum\limits_{k=1}^nk\right|\stackrel{(3)}{=}\sum\limits_{k=1}^nk](https://tex.z-dn.net/?f=%3D%5Cleft%7C%5Cdfrac%7Bn%5E2%7D%7B2%7D%2Bn-%5Cdfrac%7Bn%7D%7B2%7D%5Cright%7C%3D%5Cleft%7C%5Cdfrac%7Bn%5E2%7D%7B2%7D%2B%5Cdfrac%7Bn%7D%7B2%7D%5Cright%7C%3D%5Cleft%7C%5Cdfrac%7Bn%5E2%2Bn%7D%7B2%7D%5Cright%7C%3D%5Cleft%7C%5Cdfrac%7Bn%28n%2B1%29%7D%7B2%7D%5Cright%7C%5Cstackrel%7B%282%29%7D%7B%3D%7D%5C%5C%5C%5C%5C%5C%5Cstackrel%7B%282%29%7D%7B%3D%7D%0A%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5Enk%5Cright%7C%5Cstackrel%7B%283%29%7D%7B%3D%7D%5Csum%5Climits_%7Bk%3D1%7D%5Enk)
So in this case we prove, that:
![\left|\sum\limits_{k=1}^n(-1)^k\cdot k^2\right|=\sum\limits_{k=1}^nk](https://tex.z-dn.net/?f=%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5En%28-1%29%5Ek%5Ccdot%20k%5E2%5Cright%7C%3D%5Csum%5Climits_%7Bk%3D1%7D%5Enk)
2) n is odd.
Here,
![S_n^-](https://tex.z-dn.net/?f=S_n%5E-)
has more terms than
![S_n^+](https://tex.z-dn.net/?f=S_n%5E%2B)
. For example if n=7 then:
![S_7^-=\underbrace{1^2+3^2+5^2+7^2}_{\frac{n+1}{2}=\frac{7+1}{2}=4}\\\\\\ S_7^+=\underbrace{2^2+4^4+6^2}_{\frac{n+1}{2}-1=\frac{7+1}{2}-1=3}\\\\\\](https://tex.z-dn.net/?f=S_7%5E-%3D%5Cunderbrace%7B1%5E2%2B3%5E2%2B5%5E2%2B7%5E2%7D_%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%3D%5Cfrac%7B7%2B1%7D%7B2%7D%3D4%7D%5C%5C%5C%5C%5C%5C%0AS_7%5E%2B%3D%5Cunderbrace%7B2%5E2%2B4%5E4%2B6%5E2%7D_%7B%5Cfrac%7Bn%2B1%7D%7B2%7D-1%3D%5Cfrac%7B7%2B1%7D%7B2%7D-1%3D3%7D%5C%5C%5C%5C%5C%5C)
So there is
![\dfrac{n+1}{2}](https://tex.z-dn.net/?f=%5Cdfrac%7Bn%2B1%7D%7B2%7D)
terms in
![S_n^-](https://tex.z-dn.net/?f=S_n%5E-)
,
![\dfrac{n+1}{2}-1](https://tex.z-dn.net/?f=%5Cdfrac%7Bn%2B1%7D%7B2%7D-1)
terms in
![S_n^+](https://tex.z-dn.net/?f=S_n%5E%2B)
and:
![S_n^+=\sum\limits_{k=1}^{\frac{n+1}{2}-1}(2k)^2\\\\\\ S_n^-=\sum\limits_{k=1}^{\frac{n+1}{2}}(2k-1)^2](https://tex.z-dn.net/?f=S_n%5E%2B%3D%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D-1%7D%282k%29%5E2%5C%5C%5C%5C%5C%5C%0AS_n%5E-%3D%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7D%282k-1%29%5E2)
Now, we can calculate our sum:
![\left|\sum\limits_{k=1}^n(-1)^k\cdot k^2\right|=\left|S_n^+-S_n^-\right|= \left|\sum\limits_{k=1}^{\frac{n+1}{2}-1}(2k)^2-\sum\limits_{k=1}^{\frac{n+1}{2}}(2k-1)^2\right|=\\\\\\= \left|\sum\limits_{k=1}^{\frac{n+1}{2}-1}4k^2-\sum\limits_{k=1}^{\frac{n+1}{2}}\left(4k^2-4k+1\right)\right|=\\\\\\= \left|\sum\limits_{k=1}^{\frac{n-1}{2}-1}4k^2-\sum\limits_{k=1}^{\frac{n+1}{2}}4k^2+\sum\limits_{k=1}^{\frac{n+1}{2}}4k-\sum\limits_{k=1}^{\frac{n+1}{2}}1\right|=\\\\\\](https://tex.z-dn.net/?f=%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5En%28-1%29%5Ek%5Ccdot%20k%5E2%5Cright%7C%3D%5Cleft%7CS_n%5E%2B-S_n%5E-%5Cright%7C%3D%0A%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D-1%7D%282k%29%5E2-%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7D%282k-1%29%5E2%5Cright%7C%3D%5C%5C%5C%5C%5C%5C%3D%0A%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D-1%7D4k%5E2-%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7D%5Cleft%284k%5E2-4k%2B1%5Cright%29%5Cright%7C%3D%5C%5C%5C%5C%5C%5C%3D%0A%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn-1%7D%7B2%7D-1%7D4k%5E2-%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7D4k%5E2%2B%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7D4k-%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7D1%5Cright%7C%3D%5C%5C%5C%5C%5C%5C)
![=\left|\sum\limits_{k=1}^{\frac{n-1}{2}-1}4k^2-\sum\limits_{k=1}^{\frac{n+1}{2}-1}4k^2-4\left(\dfrac{n+1}{2}\right)^2+\sum\limits_{k=1}^{\frac{n+1}{2}}4k-\sum\limits_{k=1}^{\frac{n+1}{2}}1\right|=\\\\\\= \left|-4\left(\dfrac{n+1}{2}\right)^2+4\sum\limits_{k=1}^{\frac{n+1}{2}}k-\sum\limits_{k=1}^{\frac{n+1}{2}}1\right|\stackrel{(1),(2)}{=}\\\\\\ \stackrel{(1),(2)}{=}\left|-4\dfrac{n^2+2n+1}{4}+4\dfrac{\frac{n+1}{2}\left(\frac{n+1}{2}+1\right)}{2}-\dfrac{n+1}{2}\right|=\\\\\\](https://tex.z-dn.net/?f=%3D%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn-1%7D%7B2%7D-1%7D4k%5E2-%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D-1%7D4k%5E2-4%5Cleft%28%5Cdfrac%7Bn%2B1%7D%7B2%7D%5Cright%29%5E2%2B%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7D4k-%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7D1%5Cright%7C%3D%5C%5C%5C%5C%5C%5C%3D%0A%5Cleft%7C-4%5Cleft%28%5Cdfrac%7Bn%2B1%7D%7B2%7D%5Cright%29%5E2%2B4%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7Dk-%5Csum%5Climits_%7Bk%3D1%7D%5E%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%7D1%5Cright%7C%5Cstackrel%7B%281%29%2C%282%29%7D%7B%3D%7D%5C%5C%5C%5C%5C%5C%0A%5Cstackrel%7B%281%29%2C%282%29%7D%7B%3D%7D%5Cleft%7C-4%5Cdfrac%7Bn%5E2%2B2n%2B1%7D%7B4%7D%2B4%5Cdfrac%7B%5Cfrac%7Bn%2B1%7D%7B2%7D%5Cleft%28%5Cfrac%7Bn%2B1%7D%7B2%7D%2B1%5Cright%29%7D%7B2%7D-%5Cdfrac%7Bn%2B1%7D%7B2%7D%5Cright%7C%3D%5C%5C%5C%5C%5C%5C)
![=\left|-n^2-2n-1+2\cdot\dfrac{n+1}{2}\left(\dfrac{n+1}{2}+1\right)-\dfrac{n+1}{2}\right|=\\\\\\= \left|-n^2-2n-1+(n+1)\left(\dfrac{n+1}{2}+1\right)-\dfrac{n+1}{2}\right|=\\\\\\= \left|-n^2-2n-1+\dfrac{(n+1)^2}{2}+n+1-\dfrac{n+1}{2}\right|=\\\\\\= \left|-n^2-n+\dfrac{n^2+2n+1}{2}-\dfrac{n+1}{2}\right|=\\\\\\= \left|-n^2-n+\dfrac{n^2}{2}+n+\dfrac{1}{2}-\dfrac{n}{2}-\dfrac{1}{2}\right|=\left|-\dfrac{n^2}{2}-\dfrac{n}{2}\right|=\left|-\dfrac{n^2+n}{2}\right|=\\\\\\](https://tex.z-dn.net/?f=%3D%5Cleft%7C-n%5E2-2n-1%2B2%5Ccdot%5Cdfrac%7Bn%2B1%7D%7B2%7D%5Cleft%28%5Cdfrac%7Bn%2B1%7D%7B2%7D%2B1%5Cright%29-%5Cdfrac%7Bn%2B1%7D%7B2%7D%5Cright%7C%3D%5C%5C%5C%5C%5C%5C%3D%0A%5Cleft%7C-n%5E2-2n-1%2B%28n%2B1%29%5Cleft%28%5Cdfrac%7Bn%2B1%7D%7B2%7D%2B1%5Cright%29-%5Cdfrac%7Bn%2B1%7D%7B2%7D%5Cright%7C%3D%5C%5C%5C%5C%5C%5C%3D%0A%5Cleft%7C-n%5E2-2n-1%2B%5Cdfrac%7B%28n%2B1%29%5E2%7D%7B2%7D%2Bn%2B1-%5Cdfrac%7Bn%2B1%7D%7B2%7D%5Cright%7C%3D%5C%5C%5C%5C%5C%5C%3D%0A%5Cleft%7C-n%5E2-n%2B%5Cdfrac%7Bn%5E2%2B2n%2B1%7D%7B2%7D-%5Cdfrac%7Bn%2B1%7D%7B2%7D%5Cright%7C%3D%5C%5C%5C%5C%5C%5C%3D%0A%5Cleft%7C-n%5E2-n%2B%5Cdfrac%7Bn%5E2%7D%7B2%7D%2Bn%2B%5Cdfrac%7B1%7D%7B2%7D-%5Cdfrac%7Bn%7D%7B2%7D-%5Cdfrac%7B1%7D%7B2%7D%5Cright%7C%3D%5Cleft%7C-%5Cdfrac%7Bn%5E2%7D%7B2%7D-%5Cdfrac%7Bn%7D%7B2%7D%5Cright%7C%3D%5Cleft%7C-%5Cdfrac%7Bn%5E2%2Bn%7D%7B2%7D%5Cright%7C%3D%5C%5C%5C%5C%5C%5C)
![=\left|-\dfrac{n(n+1)}{2}\right|=|-1|\cdot\left|\dfrac{n(n+1)}{2}\right|=\left|\dfrac{n(n+1)}{2}\right|\stackrel{(2)}{=}\left|\sum\limits_{k=1}^nk\right|\stackrel{(3)}{=}\sum\limits_{k=1}^nk](https://tex.z-dn.net/?f=%3D%5Cleft%7C-%5Cdfrac%7Bn%28n%2B1%29%7D%7B2%7D%5Cright%7C%3D%7C-1%7C%5Ccdot%5Cleft%7C%5Cdfrac%7Bn%28n%2B1%29%7D%7B2%7D%5Cright%7C%3D%5Cleft%7C%5Cdfrac%7Bn%28n%2B1%29%7D%7B2%7D%5Cright%7C%5Cstackrel%7B%282%29%7D%7B%3D%7D%5Cleft%7C%5Csum%5Climits_%7Bk%3D1%7D%5Enk%5Cright%7C%5Cstackrel%7B%283%29%7D%7B%3D%7D%5Csum%5Climits_%7Bk%3D1%7D%5Enk)
We consider all possible n so we prove that:
Answer:
$3 for seinor citizen and $4 for student
Step-by-step explanation: